Afterglow Organic Light‐Emitting Diode. Issue 4 (24th November 2015) - Kabe, Ryota; Notsuka, Naoto; Yoshida, Kou; Adachi, Chihaya
Abstract : An afterglow organic light‐emitting diode (OLED) that displays electroluminescence with long transient decay after it is turned off is demonstrated. This OLED exhibits blue and green dual emission originating from fluorescence and phosphorescence, respectively. A phosphorescence lifetime of 4.3 s is achieved.